Administering colonialism and war : the political life of Sir Andrew Clow of the Indian civil service - Alexander, Colin R (Oxford University press, 2019)
Colonialism is a dehumanizing experience for all those at the mercy of its power structures. The officers of the Indian Civil Service (ICS) were no exception. This book focuses on the role of ICS in World War II and engages in a wider debate about colonialism's impact on its administrators and subjects. 0The author looks at the events of World War II specifically in the province of Assam in India's North-East. It is here that the British and American troops were stationed as they attempted to retake Burma following Japan's invasion in 1942 and supply the Allied Chinese by road and air. The volume also focuses on how radio broadcasting was used to manufacture the Indian public's consent for the war effort and explores the horrors of the Bengal Famine and the controversies surrounding the British responses to it. 0The central character in the book's narrative is Sir Andrew Clow who was a career civil servant in India. He was the Minister for Communications during the late 1930s and early 1940s before he became the Governor of Assam in 1942.